Educators’ Perspectives about Teaching Writing to EFL Learners in Large Classrooms - Hanan Abdullah Nagi Mohammed; Wissam Lutfi Ibrahim; Amal Abdelsattar Metwally (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
The present study investigates EFL educators’ perceptions and experiences in teaching EFL writing skills in large classes, focusing on the problems they face and the techniques they use to minimize these issues and achieve course objectives. Many studies hitherto have investigated the difficulties EFL teachers face in teaching writing in large – sized classes, and they have concluded that for better communication and more individual attention to be given to students, more time and effort are needed. However, this study aims to propose diverse effective, collaborative teaching methods and strategies to upgrade the students' writing skills in large classes. The study adopts a descriptive methodology to analyze a questionnaire of 17 items on a five-point Likert-type scale given to 64 faculty members. The questionnaire includes 17 questions, 14 questions on the challenges faced by teachers and suggested strategies and the last 3 questions on the role of technology in facilitating teaching writing in large classes. The electronic questionnaire was prepared using Google forms, and the data collected was analyzed using Microsoft Excel. The main finding of the study was that the challenges faced by teachers in teaching writing in large classes can be minimized by effective teaching techniques such as collaborative learning, giving personalized feedback, engaging students in pair and group work, and utilizing technology – enhanced teaching and learning methods to facilitate the writing tasks and activities. The study provides practical insights for EFL educators to effectively implement these strategies. Additionally, it encourages further research in this area to enhance pedagogical practices and support EFL teachers in overcoming these common obstacles.